Dedicated C‐fibre viscerosensory pathways to central nucleus of the amygdala. (25th October 2016) - McDougall, Stuart J.; Guo, Haoyao; Andresen, Michael C.
Abstract : Key points: Emotions are accompanied by concordant changes in visceral function, including cardiac output, respiration and digestion. One major forebrain integrator of emotional responses, the amygdala, is considered to rely on embedded visceral afferent information, although few details are known. In the present study, we retrogradely transported dye from the central nucleus of the amygdala (CeA) to identify CeA‐projecting nucleus of the solitary tract (NTS) neurons for synaptic characterization and compared them with unlabelled, near‐neighboor NTS neurons. Solitary tract (ST) afferents converged onto NTS‐CeA second‐order sensory neurons in greater numbers, as well as indirectly via polysynaptic pathways. Unexpectedly, all mono‐ and polysynaptic ST afferent pathways to NTS‐CeA neurons were organized exclusively as either transient receptor potential cation channel subfamily V member 1 (TRPV1)‐sensitive or TRPV1‐resistant, regardless of whether intervening neurons were excitatory or inhibitory. This strict sorting provides viscerosensory signals to CeA about visceral conditions with respect to being either 'normal' via A‐fibres or 'alarm' via TRPV1 expressing C‐fibres and, accordingly, this pathway organization probably encodes interoceptive status. Abstract: Emotional state is impacted by changes in visceral function, including blood pressure, breathing and digestion. A main line of viscerosensory information processing occurs first in the nucleus of the solitary tract (NTS). In the present study conducted in rats, we examined the synaptic characteristics of visceral afferent pathways to the central nucleus of the amygdala (CeA) in brainstem slices by recording from retrogradely labelled NTS projection neurons. We simultaneously recorded neuron pairs: one dye positive (i.e. NTS‐CeA) and a second unlabelled neighbour. Graded shocks to the solitary tract (ST) always (93%) triggered EPSCs at CeA projecting NTS neurons. Half of the NTS‐CeA neurons received at least one primary afferent input (classed 'second order') indicating that viscerosensory information arrives at the CeA conveyed via a pathway involving as few as two synapses. The remaining NTS‐CeA neurons received viscerosensory input only via polysynaptic pathways. By contrast, ∼3/4 of unlabelled neighbouring neurons were directly connected to ST. NTS‐CeA neurons received greater numbers of ST‐related inputs compared to unlabelled NTS neurons, indicating that highly convergent viscerosensory signals reach the CeA. Remarkably, despite multifibre convergence, all single NTS‐CeA neurons received inputs derived from only unmyelinated afferents [transient receptor potential cation channel subfamily V member 1 (TRPV1) expressing C‐fibres] or only non‐TRPV1 ST afferent inputs, and never a combination of both. Such segregation means that visceral afferent information followed separate lines to reach the CeA. Their very different physiological activation profiles mean that these parallel visceral afferent pathways encode viscerosensory signals to the amygdala that may provide interoceptive assessments to impact on behaviours. Key points: Emotions are accompanied by concordant changes in visceral function, including cardiac output, respiration and digestion. One major forebrain integrator of emotional responses, the amygdala, is considered to rely on embedded visceral afferent information, although few details are known. In the present study, we retrogradely transported dye from the central nucleus of the amygdala (CeA) to identify CeA‐projecting nucleus of the solitary tract (NTS) neurons for synaptic characterization and compared them with unlabelled, near‐neighboor NTS neurons. Solitary tract (ST) afferents converged onto NTS‐CeA second‐order sensory neurons in greater numbers, as well as indirectly via polysynaptic pathways. Unexpectedly, all mono‐ and polysynaptic ST afferent pathways to NTS‐CeA neurons were organized exclusively as either transient receptor potential cation channel subfamily V member 1 (TRPV1)‐sensitive or TRPV1‐resistant, regardless of whether intervening neurons were excitatory or inhibitory. This strict sorting provides viscerosensory signals to CeA about visceral conditions with respect to being either 'normal' via A‐fibres or 'alarm' via TRPV1 expressing C‐fibres and, accordingly, this pathway organization probably encodes interoceptive status.